Routine Multiple Duodenal Biopsy during Endoscopy of Dyspeptic Patients Seems Unnecessary for Screening of Celiac Disease - Behforouz, Amir (Gastroenterol Res Pract, 2020)
INTRODUCTION: Celiac disease (CD) is a chronic and common cause of dyspepsia with a rising prevalence worldwide. This study is aimed at investigating the prevalence of CD in dyspeptic patients based on serology and biopsy, determining the associated factors, and assessing the necessity of regular duodenal biopsies from normal mucosa in diagnosis of CD among dyspeptic patients. METHODS: This cross-sectional study was performed on 530 adult dyspeptic patients who underwent gastroduodenoscopy in Imam Reza hospital, Mashhad, during 2016-2018. Demographic characteristics, clinical data, and laboratory analyses were extracted from hospital records. CD was diagnosed based on intestinal biopsy and serum antitissue transglutaminase (anti-TTG) levels. Mucosal lesions were classified according to the modified Marsh classification. Data were analyzed in SPSS with P < 0.05 being considered significant. RESULTS: Overall, 163 males (30.8%) and 367 females (69.2%) with an average age of 46.38 ± 15.54 years were studied. High anti-TTG levels were seen in 36 (6.8%) patients, and duodenal pathologies were seen in 23 (4.5%) patients. Fifteen (2.8%) were diagnosed with CD based on both serology and biopsy. Bloating was the most common type of dyspepsia in CD patients (7, 46.7%), followed by epigastric pain (6, 40%), and postprandial fullness (2, 13.3%). Two CD patients (13.3%) reported a positive family history for CD. Logistic regression model showed that iron deficiency anemia (IDA), anti-TTG level, and Helicobacter pylori infection were predictors of histological changes of CD, whereas IDA was the only independent predictor of CD in dyspeptic patients (OR = 17.65, 95%CI = 1.53‐202.52, and P = 0.021). CONCLUSION: CD is prevalent in dyspeptic patients, but routine biopsy from normal-appearing duodenal mucosa is not recommended for all patients. Serological studies, complete history, and careful endoscopic evaluation may provide better cost-effective clinical solutions to improve the diagnostic yield of celiac disease in dyspeptic patients.